2004
DOI: 10.1074/jbc.m406260200
|View full text |Cite
|
Sign up to set email alerts
|

Warm Temperature-sensitive Transient Receptor Potential Vanilloid 4 (TRPV4) Plays an Essential Role in Thermal Hyperalgesia

Abstract: Animals sense various ranges of temperatures by cutaneous thermal stimuli. Transient receptor potential vanilloid 4 (TRPV4) is a cation channel activated at a warm temperature (over 30°C) in exogenously expressed cells. We found in the present study that TRPV4 is essential in thermal hyperalgesia at a warm temperature in vivo. TRPV4؊/؊ and TRPV4؉/؉ mice exhibited the same latency of escape from 35-50°C hotplates. Neuronal activity in the femoral nerve, however, revealed that the number and activity level of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 28 publications
4
121
0
Order By: Relevance
“…Peripheral nerve recordings have suggested that there might be a decrease in warmth-evoked electrical activity in TRPV4 Ϫ/Ϫ mice (Todaka et al, 2004). Moreover, we demonstrated that keratinocytes cultured from these animals lack the TRPV4-like warmth-activated currents observed in wildtype keratinocytes (Chung et al, 2004).…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations
“…Peripheral nerve recordings have suggested that there might be a decrease in warmth-evoked electrical activity in TRPV4 Ϫ/Ϫ mice (Todaka et al, 2004). Moreover, we demonstrated that keratinocytes cultured from these animals lack the TRPV4-like warmth-activated currents observed in wildtype keratinocytes (Chung et al, 2004).…”
Section: Introductionmentioning
confidence: 56%
“…Ϫ/Ϫ mice failed to exhibit the same reduction in hot-plate escape latency as wild-type mice (Todaka et al, 2004). The same study suggested that there was a reduction in the activity of warmth-sensitive peripheral nerve fibers in these mice, even in the uninjured state.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…>30 °C for TRPV4) [273][274][275][276][282][283][284] and their deletion results in altered sensation of thermal stimuli [285][286][287] -although recent results suggest that their contribution to heat sensation is not essential in mice [288]. Of further importance, the thermo-sensory functions of TRPV3 and TRPV4 are apparently linked to keratinocytes; namely, the moderate warm temperature elevation, that increases the activity of TRPV3 and/or TRPV4 expressed in keratinocytes, resulted in the release of ATP release which, in turn, can transmit the thermal information toward sensory neurons [289][290][291][292].…”
Section: Trpv3 and Trpv4mentioning
confidence: 99%